2015
DOI: 10.1159/000442111
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine for Cough: a Systematic Review and Meta-Analysis

Abstract: Background: The aim of this review was to systematically assess the literature on herbal medicine for cough as a symptom of upper respiratory tract infections and common cold. Methods: The Cochrane Library, Scopus, MEDLINE/PubMed, and Embase were searched through March 2012 for RCTs testing the effects of herbal medicine for cough. Risk of bias was assessed using the Cochrane tool. Results: 34 RCTs (N = 7,083) on Pelargonium sidoides (11 RCTs), Echinacea (8 RCTs), Andrographis paniculata (6 RCTs), ivy/primrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
14

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 41 publications
0
55
0
14
Order By: Relevance
“…Available evaluations of outcomes from naturopathic practices suggest naturopathic care may improve the outcomes of patients with cardiovascular conditions, diabetes, chronic pain, autoimmune disease, mental illness, and chronic obstructive pulmonary disease [38]. While there may be evidence supporting the application of specific treatments used by naturopathic practitioners in the management of some of these conditions [39][40][41][42][43][44][45][46][47][48], further research is required to fully quantify the impact and effectiveness of naturopathic care on the clinical outcomes across the diverse health complaints clinicians appear to be treating. Additionally, while all of conditions identified in this recent review are among those reported in our study as the primary reason patients have visited with naturopathic practitioners, there are also numerous conditions for which naturopathic care has not been examined.…”
Section: Resultsmentioning
confidence: 99%
“…Available evaluations of outcomes from naturopathic practices suggest naturopathic care may improve the outcomes of patients with cardiovascular conditions, diabetes, chronic pain, autoimmune disease, mental illness, and chronic obstructive pulmonary disease [38]. While there may be evidence supporting the application of specific treatments used by naturopathic practitioners in the management of some of these conditions [39][40][41][42][43][44][45][46][47][48], further research is required to fully quantify the impact and effectiveness of naturopathic care on the clinical outcomes across the diverse health complaints clinicians appear to be treating. Additionally, while all of conditions identified in this recent review are among those reported in our study as the primary reason patients have visited with naturopathic practitioners, there are also numerous conditions for which naturopathic care has not been examined.…”
Section: Resultsmentioning
confidence: 99%
“…EOC are highly bioactive aromatic components of plants and exert a wide range of proposed biological activities including antioxidative, antimicrobial, and anti-inflammatory properties as well as antigenotoxicity and anticarcinogenicity (Ait-Ouazzou et al, 2011;Bardaweel, Tawaha, & Hudaib, 2014;Bidinotto et al, 2011;Dörsam, Wu, Efferth, Kaina, & Fahrer, 2015;Teixeira et al, 2011). EO and EOC have been utilized as antimicrobials in cosmetics and toiletries (Muyima, Zulu, Bhengu, & Popplewell, 2002), foods (Tongnuanchan & Benjakul, 2014), and animal feed (Wallace et al, 2010), and are also used in alternative and complementary therapy (Ali et al, 2015;Wagner et al, 2015). Furthermore, EO and EOC have been postulated as therapeutics against colonic diseases and bac-terial infection in the human intestine (Baker et al, 2012;Koch, 1998;Rahimi, Mozaffari, & Abdollahi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Спазмолитическая и секретолитическая активность травы тимьяна при лечении кашля у 7083 лиц в возрасте от 1 до 86 лет была подтверждена в метаанализе с оценкой симптома кашля по шкале TDSS, проведенном L. Wagner с соавт. [35], и имеет убедительный уровень доказательности согласно Кокрановскому обзору (OR = 1,4; 95% ДИ 1,23-1,6; p < 0,001).…”
Section: противокашлевый эффектunclassified